2020
DOI: 10.1038/s41416-020-0942-3
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced bystander and abscopal effects: important lessons from preclinical models

Abstract: Radiotherapy is a pivotal component in the curative treatment of patients with localised cancer and isolated metastasis, as well as being used as a palliative strategy for patients with disseminated disease. The clinical efficacy of radiotherapy has traditionally been attributed to the local effects of ionising radiation, which induces cell death by directly and indirectly inducing DNA damage, but substantial work has uncovered an unexpected and dual relationship between tumour irradiation and the host immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 109 publications
0
74
0
2
Order By: Relevance
“…Furthermore, RT releases cytokines, which have been shown to play a vital role in the abscopal effect [206]. Bystander effects are mediated by several mechanisms, like direct gap-junction mediated cell-cell communication via ions such as calcium or nitric oxide, though immune factors like transforming growth factor-β and cytokines can also be released in the extracellular compartment and trigger local immune activation [207]. Macrophages also play an important role in the bystander effect: once they are activated by radiation, they damage neighboring cells by transferring different signaling factors [208][209][210].…”
Section: Radiotherapy and Abscopal Effectsmentioning
confidence: 99%
“…Furthermore, RT releases cytokines, which have been shown to play a vital role in the abscopal effect [206]. Bystander effects are mediated by several mechanisms, like direct gap-junction mediated cell-cell communication via ions such as calcium or nitric oxide, though immune factors like transforming growth factor-β and cytokines can also be released in the extracellular compartment and trigger local immune activation [207]. Macrophages also play an important role in the bystander effect: once they are activated by radiation, they damage neighboring cells by transferring different signaling factors [208][209][210].…”
Section: Radiotherapy and Abscopal Effectsmentioning
confidence: 99%
“…In particular, in the last model (glioma), the study consisted of the induction of two tumors (located in diametrically opposite positions in the mouse's abdomen) followed by applying an AMF of 30.6 kA.m À1 (ffi 384 Oe) and 118 kHz. Magnetic nanoparticles were injected in only one of the two tumors and, according to the authors, in some cases on the 28th day after the treatment by MNH a complete remission of both tumors of the animals had occurred (see Table 2), i.e., the authors observed an abscopal effect [40,[137][138][139][140]. Killing tumor cells with heat also induced a strong host immune response.…”
Section: In Vivo Mnh: Clinical Safety Criteria and Preclinical Resultmentioning
confidence: 96%
“…7 Radiation exerts lethal DNA damage in irradiated tumor cells, which improves outcomes of these patients in terms of local control. 8 However, not all patients could benefit from RT, with a considerable of LUAD patients showing radioresistance and suffering from tumor metastasis. 9 Combined application of tumor RT and ICIs has achieved enormous progress in enhancing antitumor treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 77% lung cancer patients received RT, 7 which elicits DNA damage and immunogenic cell death, induces tumor neoantigen release, and activates immune system. 8 However, the therapeutic effects of RT is unsatisfactory due to radioresistance. A considerable proportion of LUAD patients has relapses followed by RT.…”
Section: Introductionmentioning
confidence: 99%